Die betekenis en doel van finansiële beheer en verantwoording by munisipaliteite in Suid-Afrika (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
With a corruption perception index score of 5.4, South Africa is ranked as one of the most corrupt countries in the world and this does not bode well for the country’s development. Most municipalities in South Africa are under pressure as a result of poor financial control and accoun ta bility that give cause to extensive corruption and financial mismanage ment with subsequent detrimental consequences for effective and efficient service delivery to the community. Financial control and ac coun tability are of utmost importance in determining either the success or failure of local government. Ethical conduct and the acceptance of proper values can contribute towards sound financial management at municipalities and can prohibit municipal councillors and officials to be attracted to corrupt activities. If municipalities want to overcome the current challenges, it is essential for those involved to address these matters in a sincere, honest and ethical manner. In this article the author investigates the meaning and purpose of financial control and accoun ta bility as a value-driven norm for accountable and ethical local govern ment in South Africa.